Vaginal health and hygiene practices and product use in Canada: a national cross-sectional survey - Sara E. Crann; Shannon Cunningham; Arianne Albert; Deborah M. Money; Kieran C. O'Doherty (BMC, 2018)
Abstract Background The vaginal microbiome influences quality of life and health. The composition of vaginal microbiota can be affected by various health behaviors, such as vaginal douching. The purpose of this study was to examine the types and prevalence of diverse vaginal/genital health and hygiene behaviors among participants living in Canada and to examine associations between behavioral practices and adverse gynecological health conditions. Method An anonymous online survey, available in English and French, was distributed across Canada. The sample consisted of 1435 respondents, 18 years or older, living in Canada. Results Respondents reported engaging in diverse vaginal/genital health and hygiene behavioral practices, including the use of commercially manufactured products and homemade and naturopathic products and practices. Over 95% of respondents reported using at least one product in or around the vaginal area. Common products and practices included vaginal/genital moisturizers, anti-itch creams, feminine wipes, washes, suppositories, sprays, powders, and waxing and shaving pubic hair. The majority of the sample (80%) reported experiencing one or more adverse vaginal/genital symptom in their lifetime. Participants who had used any vaginal/genital product(s) had approximately three times higher odds of reporting an adverse health condition. Several notable associations between specific vaginal/genital health and hygiene products and adverse health conditions were identified. Conclusions This study is the first of its kind to identify the range and prevalence of vaginal/genital health and hygiene behaviors in Canada. Despite a lack of credible information about the impact of these behaviors on women's health, the use of commercially manufactured and homemade products for vaginal/genital health and hygiene is common. Future research can extend the current exploratory study by identifying causal relationships between vaginal/genital health and hygiene behaviors and changes to the vaginal microbiome.